Exposição crônica a uma mistura de desreguladores endócrinos altera o fenótipo nuclear e induz fibrose renal em ratos - Hinokuma, Karianne Delalibera (2023)
Synthetic compounds have long been introduced into human everyday life. The exposome concept has been proposed as the assessment of environmental exposures and associated biological responses over a lifetime. Disseminated in the environment, endocrine disruptors (ED) are capable of modifying hormone biosynthesis, which may cause instabilities in human health. Because they have bioaccumulation as their main characteristic, the kidney becomes a potential target of ED. Thus, researches using experimental protocols that mimic human exposure throughout life are important to characterize the effects of ED on health/homeostasis, especially in the kidney, an important organ within this internal balance system. Thus, the aim of the present study was to evaluate cellular and tissue changes, in addition to oxidative stress, in the kidney of rats exposed during pregnancy, lactation and even adulthood to an ED mixture based on human exposure. Pregnant females of the Sprague-Dawley strain were randomly divided into 2 experimental groups: Ctrl Group (vehicle: corn oil, by gavage) and ED Mix group: they received 32.11mg/kg/day of a mixture consisting of twelve compounds (phthalates, pesticides , u.v. filters, bisphenol A, butylparaben) diluted in corn oil (2ml/kg), by gavage. Pregnant or lactating rats received the treatment from gestational day 7 (DG7) until postnatal day 21 (DPN21). After weaning, at DPN22, the male offspring of the F1 generation continued to receive the complete EDmixture until they were 220 days old, when they were euthanized. The kidney was collected, dissected and processed for histological analysis. Sections stained with hematoxylin-eosin and picrosirius were submitted to fractal and kariometric analysis, analysis of glomerular volume, nuclear perimeter, elongation factor and quantification of collagen types. In addition, oxidative stress was performed. No changes were observed in the biometric data. Nuclear alterations were dependent on the evaluated compartment, with the ED mixture favoring the presence of elliptical nuclei in the cortical and glomerular region and more rounded nuclei in the medullary region. ED mixture caused an increase in renal fibrosis in all compartments, without altering antioxidant enzymes. In view of this, we conclude that environmentally relevant exposure to a ED mixture causes nuclear changes and induces renal fibrosis.